THE UBHI CASE DOES NOT SIGNIFY THAT CLAIMS BASED ON ETS EXPOSURE ARE LEGALLY VIABLE (Tufts Archival Research Center, 2007)
Report on Ubhi v. State Compensation Insurance Fund. Finds that secondhand smoke exposure at Ubhi's workplace could not be considered a cause of his heart attack.